Performance analysis of seven level multilevel inverter for power quality improvement - Priya, S. Nithya; Ramya, K. C. (International Journal of Applied Power Engineering (IJAPE), 2025)
Power conversion systems for demanding applications requiring high power and power quality are increasingly using multi-level converters. Due to its many advantages, such as low harmonic content, low electromagnetic interference (EMI) output, and low power consumption in power switches, the multilayer inverter (MLI) topology is more commonly used in medium and high power applications. The chosen switching technique of the inverter for operation significantly contributes to the suppression of harmonic components while creating the optimal output voltage. A single-phase 7-level cascaded H-bridge multilevel inverter (CHB-MLI) with fewer switches and alternative control algorithms is available in MATLAB-based simulation on the SIMULINK platform. In this research, the total harmonic distortion (THD) of several control techniques is compared. From the simulation results, it was found that the proposed artificial neural network (ANN) controller outperforms the proportional-integral (PI) controller. With a lower THD value and a comparatively better sinusoidal waveform, the ANN controller produces an output voltage. It is also more suitable for improving the quality of electricity. The efficiency and performance of the proposed 7-level CHBMI system are demonstrated by the improved sinusoidal output waveform and reduced output voltage THD.